Analysis of the Effectiveness of Value Added Tax Policy for Health Services at PT Kimia Farma Diagnostika in 2021 - Pasaribu , Maria Jeremiah (Indonesian Scientific Publication, 2023)
This study aims to analyze the effectiveness of the VAT policy using James L. Gibson's theory of effectiveness in the form of efficiency, development, and the advantages of the applied Value Added Tax policy. Researchers will also see if there are any obstacles experienced and the efforts that will be applied. This research will be conducted at PT Kimia Farma Diagnostika using a qualitative descriptive method. This research data will be obtained using primary and secondary data from interviews and direct observations at PT Kimia Farma Diagnostika.